2017
DOI: 10.1158/2159-8290.cd-16-1223
|View full text |Cite
|
Sign up to set email alerts
|

Primary Resistance to PD-1 Blockade Mediated by JAK1/2 Mutations

Abstract: Loss of function mutations in JAK1/2 can lead to acquired resistance to anti-programmed death protein 1 (PD-1) therapy. We reasoned they may also be involved in primary resistance to anti-PD-1 therapy. JAK1/2 inactivating mutations were noted in tumor biopsies of 1 of 23 patients with melanoma and in 1 of 16 patients with mismatch repair deficient colon cancer treated with PD-1 blockade. Both cases had a high mutational load but did not respond to anti-PD-1 therapy. Two out of 48 human melanoma cell lines had … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
858
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,073 publications
(931 citation statements)
references
References 49 publications
26
858
2
1
Order By: Relevance
“…Analyses of tumours with a very low IFNγ-associated geneexpression score, or a 'non-T-cell-inflamed' tumour microenvironment have revealed roles for activation of the WNT/β-catenin-signalling pathway 145 , and an enrichment for mutations in PTEN 146 in immune evasion. Deleterious mutations in the genes encoding JAK1 and JAK2 (which are involved in IFNγ signalling), or β 2 microglobulin (an MHC class I subunit), as well as loss of expression of interferon regulatory factor 1 (IRF1) have also been described in anti-PD-1-antibody-resistant patient samples and cell lines 147,148 . These intratumoural changes are associated with deficits in autophagy, antigen presentation, and the type I interferon response, suggesting that rational drug combinations should be explored to either suppress these pathways using β-catenin or PI3Kβ inhibitors, and/or amplify antigen presentation, perhaps via an approach such as FLT3-ligand agonism.…”
Section: Braf-mek-inhibitor Resistance and Biomarkersmentioning
confidence: 99%
“…Analyses of tumours with a very low IFNγ-associated geneexpression score, or a 'non-T-cell-inflamed' tumour microenvironment have revealed roles for activation of the WNT/β-catenin-signalling pathway 145 , and an enrichment for mutations in PTEN 146 in immune evasion. Deleterious mutations in the genes encoding JAK1 and JAK2 (which are involved in IFNγ signalling), or β 2 microglobulin (an MHC class I subunit), as well as loss of expression of interferon regulatory factor 1 (IRF1) have also been described in anti-PD-1-antibody-resistant patient samples and cell lines 147,148 . These intratumoural changes are associated with deficits in autophagy, antigen presentation, and the type I interferon response, suggesting that rational drug combinations should be explored to either suppress these pathways using β-catenin or PI3Kβ inhibitors, and/or amplify antigen presentation, perhaps via an approach such as FLT3-ligand agonism.…”
Section: Braf-mek-inhibitor Resistance and Biomarkersmentioning
confidence: 99%
“…Ipilimumab-refractory melanoma tumors were insensitive to IFN-γ signaling due to mutations in IFNGR1, IFNGR2, JAK2, and interferon regulatory factor 1 (IRF1) which is responsible for the INF-γ-induced upregulation of PD-L1 (86). Mutations in JAK1 and JAK2 were also found in melanoma and colorectal cancer patients who failed to respond to anti-PD1 despite having tumors with high mutational load (87,88). Similar mutations in JAK1 and JAK2 were also detected in relapsing tumors from melanoma patients who initially responded to anti-PD-1 therapy, indicating that loss of responsiveness to IFN-γ signaling may be a potential tumor escape mechanism contributing to relapse following immune checkpoint blockade (81).…”
Section: Mechanisms Of Resistance To Immune Checkpoint Blockadementioning
confidence: 99%
“…JAK1/2 loss of function mutations may have important role in the absence of response to PD-1 inhibitors due to lower ability of immune T cells to recognize tumor cells. It has also been shown that these mutations may result in a lack of T-cell infiltrates due to deficit of chemokine production [8]. Zaretsky et al showed that loss-of-function mutations of JAK1/2 encoding IFN-γ receptor were implicated in acquired resistance to pembrolizumab in the management of metastatic melanoma.…”
Section: Primary Resistance To Icimentioning
confidence: 99%